Combining laser capture microdissection and proteomics reveals an active translation machinery controlling invadosome formation - Zakaria Ezzoukhry (Nature Portfolio, 2018)
Invadosomes degrade extracellular matrix and facilitate cell invasion but their molecular composition is not fully understood. Here, the authors combine laser capture and mass spectrometry to map the proteome of invadosomes, showing that they rely on internal translational activity to maintain their structure.